Transformasi perpustakaan untuk generasi millenial menuju revolusi industri 4.0 - Catur Khadijah (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2018)
This article discusses library transformation for the millennial generation towards industrial revolution 4.0. The occurrence of the 4th industrial revolution made technology develop extraordinary, while bringing positive and negative effects to humans. The development of these technologies also influenced the use of social media in the community. So is the library. The collection of digital libraries must also be developed not all books, magazines, or journals but other content that can satisfy the thirst of knowledge for users. The existence of Virtual Reality devices allows libraries to have a collection of libraries that are more interesting and visible to the community. Virtual Reality content is not only available on the internet or content provider services, but can also be independently developed through applications that are often available free on the internet. Keywords: millennial generation; library, industrial revolution 4.0